3x=-x-1

Simple and best practice solution for 3x=-x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x=-x-1 equation:


3x=-x-1

We simplify the equation to the form, which is simple to understand
3x=-x-1

We move all terms containing x to the left and all other terms to the right.
+3x+1x=-1

We simplify left and right side of the equation.
+4x=-1

We divide both sides of the equation by 4 to get x.
x=-0.25

See similar equations:

| 74%222=n | | 2x+5x^2=35 | | 74%222= | | 3x-2+y=0 | | =217s-7 | | 2x+5x^2=30 | | a+-4a+-3a= | | -x+4=-y | | 2x+15x^2=24 | | 7.6-0.7h+1.2-1.3h=24-2.0h-6.7 | | 6.9x-3.6=24.0 | | 6y^2=-7-2 | | 8/3x-21/2 | | 2x+15x^2=32 | | 5x5/5/7 | | 128=8-4e | | 45x+27= | | 2x+15x^2=35 | | x^3+5x^2-4x-2=0 | | 25=-5y-6x | | -6w^2+150w=0 | | 5(2x-17)=10x-85 | | 5x+x^2=y | | -13+3x+4+-5x=15 | | 0.06x-0.10(x-2)=0.02(8) | | 36+7-25+7= | | 4x-15/3=7 | | -2(7x-4)+3(5x-4)-3=7-3 | | 28+p=39 | | 10g+10=29g | | 17.40=1.5n | | 3y=8-2x |

Equations solver categories